Vocal Folds Leukoplakia: The Efficacy of Vitamin a in the Initial Treatment - Botini, Dayane Silvestre [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Castilho, Gustavo Leao [UNESP]; Mercuri, Gustavo [UNESP]; Martins, Regina Helena Garcia [UNESP] (Georg Thieme Verlag Kg, 2022)
Introduction Laryngeal leukoplakia corresponds to a white lesion in the mucosa developed by the deposit of keratin in the epithelium, potentiated by chronic smoking. It is considered a preneoplastic lesion. Surgery is the most adopted treatment; however, non-surgical treatment is advocated by some authors. Objective To evaluate the effectiveness of vitamin A in the management of vocal fold leukoplakia. Methods Patients with videolaryngoscopy diagnosis of vocal fold leukoplakia were selected. The endoscopic images were photographed and with the aid of the ImageJ software (National Institutes of Health, Bethesda, MD, USA), the proportion of the size of the leukoplakia was calculated. Eligible patients were prescribed 50,000U of vitamin A, twice daily for 2 months, at which point videolaryngostroboscopy was repeated for comparative analysis between pre and posttreatment. The efficacy of the treatment was classified as: outcome I - complete improvement of the lesion, outcome II - partial improvement, and outcome III - no difference or increased lesion size. Results Fifteen patients (eight women, seven men) were included, six of whom had bilateral lesions. Smoking was reported in 86.8% of patients. Complete improvement of the lesion was found in 7 cases (33.4%, outcome I), partial improvement in 6 (28.6%, outcome II), and worsening of the injury in 8 (38.1%, outcome III). Of the latter, 6 underwent microsurgery; histopathology indicated absence of dysplasia in 3, and mild dysplasia in 3. Conclusions In this study, the treatment with vitamin A at a dose of 100,000IU daily for 2 months was effective in reducing the laryngeal leukoplakia size in 62% of cases.
Keywords: leukoplakia; vocal folds; larynx; vitamin A; treatment